Severe acute respiratory distress syndrome in a case of congenital tuberculosis with congenital cytomegalovirus infection complicated with secondary hemophagocytic lymphohistiocytosis - A S Deepa; Prabhas Prasun Giri; Priyankar Pal (Wolters Kluwer Medknow Publications, 2020)
Congenital tuberculosis (CT) is rare and is transmitted to the fetus hematogenously through the umbilical vein or by fetal aspiration or ingestion of infected amniotic fluids prior to or during delivery. Congenital cytomegalovirus (cCMV) infections are defined as those infections which are acquired through transplacental entry of organism from maternal blood stream into the fetus or transmitted during passage through the birth canal. We report the case of a 4½-month-old baby presented with fever and respiratory symptoms with hepatosplenomegaly and diagnosed to be a case of CT with cCMV infection further complicated by secondary hemophagocytic lymphohistiocytosis and severe acute respiratory distress syndrome and salvaged by high-frequency oscillatory ventilation, antitubercular drugs, and steroids.